Estudio de pre-factibilidad de lavandería para el programa de Residencias Estudiantiles del Tecnológico de San Carlos - Arias-Mendoza, Yanin (Instituto Tecnológico de Costa Rica, 2015)
This feasibility study takes place in “Tecnológico de Costa Rica, Sede San Carlos.” Specifically, in the Residences Student Program, which is responsible for providing accommodation for university students that for some reasons, they have a difficulty to travel from their homes. The main objective of the feasibility study focuses on contributing to the Residences Student Program in making decisions respect to laundry service developed in the present study. With this, this study validates the feasibility of implementing a laundry that considers the needs of current students. The methodology used focusing on the development of different studies in which established specific variables. These were also described with analyzed information that was relevant to achieve the objectives of this study. This investigation concludes that the Modernization Project of Laundry is feasible because this presents a demand for the service. Furthermore, this study does not take into account legal or environmental impediments to discredit or slow the project.
Proyecto de graduación (Bachillerato en Administración de Empresas) Instituto Tecnológico de Costa Rica, Escuela Administración de Empresas, 2015
Keywords: Estudios de factibilidad; Servicios; Lavandería